2018
DOI: 10.1371/journal.pone.0195146
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of gestational age, area deprivation and mother’s country of birth to ethnic variations in infant mortality in England and Wales: A national cohort study using routinely collected data

Abstract: ObjectivesWe aimed to describe ethnic variations in infant mortality and explore the contribution of area deprivation, mother’s country of birth, and prematurity to these variations.MethodsWe analyzed routine birth and death data on singleton live births (gestational age≥22 weeks) in England and Wales, 2006–2012. Infant mortality by ethnic group was analyzed using logistic regression with adjustment for sociodemographic characteristics and gestational age.ResultsIn the 4,634,932 births analyzed, crude infant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…All Mixed groups and ‘Other’ groups were aggregated because of small numbers and the complexity of the heterogeneous composition of the subgroups which would have made any results difficult to interpret. Details of the derivation of the ethnic group categories are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All Mixed groups and ‘Other’ groups were aggregated because of small numbers and the complexity of the heterogeneous composition of the subgroups which would have made any results difficult to interpret. Details of the derivation of the ethnic group categories are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…This has shown that compared with White mothers, the risks of preterm birth are consistently higher for Black mothers but similar or lower for East Asian and Hispanic mothers . Health disparities between ethnic groups have also been observed in England and Wales . In particular, the risk of preterm birth, especially very preterm birth, is high among mothers of Caribbean and West African origin compared with White mothers .…”
Section: Introductionmentioning
confidence: 97%
“…After exclusions for implausible gestational age (0.4%), missing birth weight (0.4%) and implausible birth weight (1.5%), there were 4 634 932 live singleton births,16 of which 256 142 were at 24–36 completed weeks of gestation (table 1). The proportion of births in the ‘unstated’ category of ethnicity was 6%, decreasing from 10% in 2006 to 4% in 2012.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a national cohort study using routine data provided by the Office for National Statistics (ONS), based on National Health Service birth notifications linked with civil birth and death registrations. Details are reported elsewhere 16. The full cohort comprised all 4.7 million singleton babies born alive at 22+ completed weeks of gestation in England and Wales from 1 January 2006 to 31 December 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation